Positive electrode active material for lithium secondary battery, its manufacturing method, positive electrode and lithium secondary battery including the same

A bimodal distribution of secondary particles with a lithium M oxide coating layer addresses the cracking issue in lithium secondary batteries, enhancing rolling density and stability by ensuring the cohesive force between giant primary particles is weaker than fine primary particles, thereby improving the life characteristics.

JP7607776B2Active Publication Date: 2024-12-27LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023538142
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-15
Filing Date
2022-01-14
Publication Date
2024-12-27
Estimated Expiration
2042-01-14

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face issues with cracking of secondary particles during the rolling process due to the use of secondary particles formed by agglomerating fine primary particles, leading to decreased stability and thermal stability, particularly in high-Ni lithium transition metal oxides.

Method used

A positive electrode active material is developed with a bimodal distribution of secondary particles, comprising large secondary particles and small secondary particles with a lithium M oxide coating layer, where the average particle sizes differ, and the cohesive force between giant primary particles of the small secondary particles is weaker than that of fine primary particles, preventing cracking during rolling.

Benefits of technology

The bimodal distribution of particles with a lithium M oxide coating layer enhances rolling density and improves the life characteristics of lithium secondary batteries by preventing cracking and maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607776000004
    Figure 0007607776000004
  • Figure 0007607776000005
    Figure 0007607776000005
  • Figure 0007607776000006
    Figure 0007607776000006
Patent Text Reader

Abstract

The present invention relates to a method for producing a lithium-ion-sintered powder comprising: a) a secondary small particle having an average particle diameter (D50) of 1 to 10 μm, which is formed by agglomerating large primary particles having an average particle diameter (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is at least one selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface; and b) a secondary large particle having an average particle diameter (D50) of 5 to 20 μm, which is formed by agglomerating fine primary particles having an average particle diameter (D50) smaller than that of the large primary particles; a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, which contains primary large particles, and a method for producing the same.

[0002] This application claims priority to Korean Patent Application No. 10-2021-0006202, filed on January 15, 2021, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] In recent years, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have relatively high capacity has been rapidly increasing. In particular, lithium secondary batteries are lightweight and have high energy density, and are in the spotlight as a driving power source for portable devices. Therefore, research and development to improve the performance of lithium secondary batteries has been actively conducted.

[0004] A lithium secondary battery generates electrical energy by oxidation and reduction reactions occurring when lithium ions are inserted / deintercalated at the positive and negative electrodes, with an organic or polymer electrolyte filled between the positive and negative electrodes, which are made of active materials capable of intercalating and deintercalating lithium ions.

[0005] Lithium cobalt oxide (LiCoO2), nickel-based lithium transition metal oxides, lithium manganese oxides (LiMnO2 or LiMn2O4, etc.), and lithium iron phosphate compounds (LiFePO4) are used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its advantages of high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage. However, due to the rising price of cobalt (Co) and unstable supply, there is a limit to its large-scale use as a power source in fields such as electric vehicles, and the development of an alternative positive electrode active material is required. In particular, a positive electrode active material made of a high-nickel-content (Ni-rich) lithium composite transition metal oxide is attracting attention in terms of its high capacity.

[0006] Currently, the commercially available nickel-containing lithium transition metal composite oxide positive electrode active material uses secondary particles formed by agglomeration of fine primary particles with an average particle size (D50) of several hundred nm. In order to increase output and rolling density, a bimodal positive electrode active material is usually used, which is a mixture of two types of secondary particles with different average particle sizes (D50), i.e., secondary large particles with a large average particle size and secondary small particles with a small average particle size.

[0007] Secondary particles, which are the agglomeration of fine primary particles, have a large specific surface area and low particle strength. Therefore, when an electrode is manufactured from the bimodal positive electrode active material and then rolled, there is a problem that the secondary large particles crack severely, which causes a large amount of gas generation during cell operation and a decrease in stability. In the case of high-nickel-based (high-Ni) lithium transition metal oxides, in which the nickel (Ni) content is increased to ensure high capacity, if particle cracks occur due to structural problems, chemical stability is further reduced and thermal stability is also difficult to ensure. Summary of the Invention [Problem to be solved by the invention]

[0008] The problem to be solved by the present invention is to provide a positive electrode active material comprising a high-content nickel-based lithium transition metal oxide that contains secondary particles having different average particle sizes and can improve cracking during rolling and life characteristics.

[0009] In addition, the problem to be solved by the present invention is to provide a method for manufacturing a positive electrode active material comprising a high-content nickel-based lithium transition metal oxide that contains secondary particles having different average particle sizes and can improve cracking during rolling and life characteristics.

[0010] Another object of the present invention is to provide a positive electrode and a lithium secondary battery including a positive electrode active material made of a high content of nickel-based lithium transition metal oxide having the above-mentioned characteristics. [Means for solving the problem]

[0011] An aspect of the present invention provides a positive electrode active material for a lithium secondary battery according to the following embodiment.

[0012] The first embodiment is secondary small particles having an average particle size (D50) of 1 to 10 μm, which are formed by agglomeration of large primary particles having an average particle size (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface; and secondary large particles having an average particle size (D50) of 5 to 20 μm formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the large primary particles, The large primary particles and the fine primary particles are Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ(1.0 ≦ a ≦ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≦ d ≦ 0.1, 0 < b + c + d ≦ 0.2, -0.1 ≦ δ ≦ 1.0, where Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr) relates to a positive electrode active material for a lithium secondary battery.

[0013] A second embodiment is, in the first embodiment, relates to a positive electrode active material for a lithium secondary battery in which the ratio of the average particle diameter (D50) of the secondary large particles to the average particle diameter (D50) of the secondary small particles is 5:1 to 2:1.

[0014] A third embodiment is, in the first or second embodiment, relates to a positive electrode active material for a lithium secondary battery in which the content of the secondary small particles is 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles.

[0015] A fourth embodiment is, in any one of the first to third embodiments, relates to a positive electrode active material for a lithium secondary battery in which M in the lithium M oxide coating layer is one or more selected from the group consisting of boron and cobalt.

[0016] A fifth embodiment is, in any one of the first to fourth embodiments, relates to a positive electrode active material for a lithium secondary battery in which the content of M in the lithium M oxide coating layer is 0.05 to 10 parts by weight based on 100 parts by weight of the secondary small particles.

[0017] A sixth embodiment is, in any one of the first to fifth embodiments, relates to a positive electrode active material for a lithium secondary battery in which the cohesive force between the giant primary particles of the secondary small particles is smaller than the cohesive force between the fine primary particles of the secondary large particles.

[0018] Another aspect of the present invention provides a method for manufacturing a positive electrode active material for a lithium secondary battery according to the following embodiments.

[0019] A seventh embodiment is, (S1) Mix a transition metal-containing solution containing nickel, cobalt, manganese, and Q (Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr) in a predetermined molar ratio with an aqueous ammonia solution and a basic aqueous solution to form transition metal hydroxide precursor particles, separate and dry them, and then grind the transition metal hydroxide precursor particles so as to have a predetermined average particle size (D50). (S2) Mix the ground transition metal hydroxide precursor particles with a lithium raw material substance and bake them in an oxygen atmosphere to produce core fine particles represented by Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and the average particle size (D50) is 0.5 to 3 μm, and the core fine particles in which the giant primary particles are aggregated. (S3) Mix a solution of a precursor containing one or more selected from the group consisting of boron, cobalt manganese, and magnesium with the core fine particles, then spray and dry using a spray dryer, and then bake in an oxygen atmosphere to produce secondary fine particles with an average particle size (D50) of 0.5 to 3 μm, and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) is formed on part or all of the surface. The average particle size (D50) is 1 to 10 μm. (S4) Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ(1.0 ≦ a ≦ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≦ d ≦ 0.1, 0 < b + c + d ≦ 0.2, -0.1 ≦ δ ≦ 1.0, and Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and secondary large particles having an average particle diameter (D50) of 5 to 20 μm formed by aggregating fine primary particles having an average particle diameter (D50) smaller than that of the giant primary particles are prepared and mixed with the secondary small particles. The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery.

[0020] Example 8 is, in Example 7, The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, wherein the ratio of the average particle diameter (D50) of the secondary large particles to the average particle diameter (D50) of the secondary small particles is 5:1 to 2:1.

[0021] Example 9 is, in Example 7 or Example 8, The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, wherein the content of the secondary small particles is 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles.

[0022] Example 10 is, in any one of Examples 7 to 9, The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, wherein M in the lithium M oxide coating layer is one or more selected from the group consisting of boron and cobalt.

[0023] Example 11 is, in any one of Examples 7 to 10, The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, wherein the content of M in the lithium M oxide coating layer is 0.05 to 10 parts by weight based on 100 parts by weight of the secondary small particles.

[0024] Example 12 provides a positive electrode for a lithium secondary battery including the above-described positive electrode active material.

[0025] Example 13 provides a lithium secondary battery including the above-described positive electrode.

Advantages of the Invention

[0026] The cathode active material according to one embodiment of the present invention has a good rolling density by including both secondary large particles and secondary small particles. In addition, the secondary small particles having a predetermined average particle size, which are aggregates of large primary particles having a coating layer formed on the surface, improve the cracking phenomenon of the secondary large particles by allowing a part of the primary particles to fall off and separate before the secondary large particles crack during rolling. As a result, the life characteristics of a lithium secondary battery including the cathode active material according to the present invention are improved.

[0027] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to facilitate a further understanding of the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to the matters depicted in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated to emphasize a clearer description. [Brief description of the drawings]

[0028] [Figure 1a] FIG. 2 is a schematic diagram of a secondary large particle according to the present invention. [Figure 1b] 1 is a SEM image of the secondary large particles used in Example 1. [Figure 2a] FIG. 2 is a schematic diagram of secondary small particles according to the present invention. [Figure 2b] 1 is a SEM image of the secondary small particles used in Example 1. [Figure 3a] FIG. 2 is a schematic diagram of a single particle used in Comparative Example 2. [Figure 3b] 1 is a SEM image of a single particle used in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, the embodiment of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims are not to be interpreted as being limited to their ordinary and dictionary meanings, but are to be interpreted as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the configurations shown in the embodiments described in this specification are merely the most preferable embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted therefor at the time of this application.

[0030] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.

[0031] In the present specification and claims, "comprising a large number of crystal grains" means a crystal consisting of two or more crystal grains having an average crystal size in a specific range. In this case, the crystal size of the crystal grains can be quantitatively analyzed using X-ray diffraction analysis (XRD) using CuKα X-rays (Xrα). Specifically, the average crystal size of the crystal grains can be quantitatively analyzed by placing the produced particles in a holder and analyzing the diffraction pattern produced by irradiating the particles with X-rays.

[0032] In the present specification and claims, D50 may be defined as a particle diameter at 50% of the particle size distribution, and may be measured using a laser diffraction method. For example, the average particle diameter (D50) of the positive electrode active material may be measured by dispersing the particles of the positive electrode active material in a dispersion medium, introducing the particles into a commercially available laser diffraction particle size measuring device (e.g., MT3000 manufactured by Microtrac), irradiating the particles with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle diameter (D50) corresponding to 50% of the cumulative volume in the measuring device.

[0033] In the present invention, the "primary particle" means a particle that does not have grain boundaries on its appearance when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope.

[0034] In the present invention, the "secondary particle" is a particle formed by aggregation of the primary particles.

[0035] In the present invention, the "single particle" is a particle that exists independently of the secondary particle and does not have grain boundaries on its appearance, and means, for example, a particle having a particle size of 0.5 μm or more.

[0036] In the present invention, when referring to "particles", it may mean including any one or all of single particles, secondary particles, and primary particles.

[0037] According to one aspect of the present invention, secondary fine particles having an average particle size (D50) of 1 to 10 μm, which are formed by aggregation of giant primary particles having an average particle size (D50) of 0.5 to 3 μm and having a lithium M-oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on part or all of the surface, and secondary large particles having an average particle size (D50) of 5 to 20 μm, which are formed by aggregation of fine primary particles having an average particle size (D50) smaller than that of the giant primary particles, are included, wherein the giant primary particles and the fine primary particles are Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0 ≦ a ≦ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≦ d ≦ 0.1, 0 < b + c + d ≦ 0.2, -0.1 ≦ δ ≦ 1.0, and Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and a positive electrode active material for a lithium secondary battery is provided.

[0038] <Secondary large particles> The secondary large particles are secondary particles with an average particle size (D50) of 5 to 20 μm, formed by the aggregation of fine primary particles having an average particle size (D50) smaller than that of the giant primary particles constituting the secondary small particles described later. The fine primary particles are Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, and Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), which is a cathode active material represented by

[0039] The average particle size (D50) of the fine primary particles is smaller than that of the giant primary particles constituting the secondary small particles, and usually has an average particle size (D50) in the hundreds of nm level, for example, 100 to 900 nm.

[0040] The average particle size (D50) of the secondary large particles is 5 to 20 μm, which is larger than that of the secondary small particles described later.

[0041] Such secondary large particles having such a size are generally particles used as the large particles of the bimodal cathode active material, and are manufactured by the ordinary manufacturing method described later.

[0042] As described above, such secondary large particles formed by the aggregation of fine primary particles have a large specific surface area and low particle strength. Therefore, when an electrode is manufactured by mixing with secondary small particles formed by the aggregation of fine primary particles and having an average particle size smaller than that of the secondary large particles and then rolling, there is a problem that the secondary large particles are severely cracked, the gas generation amount during cell driving is large, and the stability is reduced.

[0043] The inventors of the present invention solved such problems by mixing secondary small particles in the following form.

[0044] <Secondary small particles> The positive electrode active material of the present invention contains, together with the large particles described above, secondary small particles having an average particle size (D50) of 1 to 10 μm, which are formed by agglomeration of large primary particles having an average particle size (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface.

[0045] The positive electrode active material has improved rolling density by containing both secondary large particles and secondary small particles.

[0046] The secondary small particles according to one embodiment of the present invention refer to aggregate particles formed by agglomeration of a plurality of macro primary particles having a coating layer formed thereon.

[0047] The secondary small particles are formed by agglomeration of large primary particles having an average particle size (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface, as described in detail below.

[0048] The large primary particles constituting the secondary small particles according to one embodiment of the present invention have a larger average particle size (D50) than the fine primary particles constituting the secondary large particles. That is, the secondary small particles are in the form of secondary particles in which large primary particles, which are enlarged, are aggregated within a certain number, unlike the general form of conventional positive electrode active materials, i.e., a form in which fine primary particles having a small average particle size are aggregated to form secondary particles.

[0049] The large primary particles are those in which the average particle size and average crystal size of the primary particles have grown simultaneously, as compared with the micro primary particles that constitute conventional secondary particles.

[0050] From the viewpoint of cracks, it is advantageous to have a large average particle size without any apparent grain boundaries, like conventional single particles. If only the average particle size (D50) of the primary particles is increased by over-firing, a rock salt structure is formed on the surface of the primary particles, resulting in high initial resistance. If the crystal size of the primary particles is also grown, the resistance can be reduced. Therefore, the giant primary particles of the present invention are particles that have a large average particle size as well as a large average crystal size, and have no apparent grain boundaries.

[0051] When the average particle size and average crystal size of the primary particles grow simultaneously in this manner, the resistance is lowered and it has the advantage of a longer life, compared to conventional single particles, which have a large increase in resistance due to a rock salt structure formed on the surface when fired at high temperatures.

[0052] Thus, compared to conventional single particles, the "secondary small particles composed of aggregates of large primary particles" used in one embodiment of the present invention have the advantage of lowering resistance due to an increase in the size of the primary particles themselves and a decrease in the rock salt structure.

[0053] In this case, the average crystal size of the giant primary particles can be quantitatively analyzed using X-ray diffraction analysis (XRD) using CuKα X-rays (X-rays). Specifically, the produced particles are placed in a holder, and the average crystal size of the giant primary particles can be quantitatively analyzed by analyzing the diffraction pattern produced by irradiating the particles with X-rays. The average crystal size of the giant primary particles can be 200 nm or more, specifically 250 nm or more, and more specifically 300 nm or more.

[0054] Meanwhile, the coating layer may be formed on some or all of the surfaces of the plurality of giant primary particles, and a form in which the coating layers are connected to each other to fill all the gaps between the giant primary particles is also included as one form of the coating layer. Preferably, the coating layer is formed on all of the surfaces of the plurality of giant primary particles to fill all the gaps between the giant primary particles.

[0055] The cohesive force between the large primary particles on which the coating layer is formed is weaker than the force at which the secondary large particles break, i.e., the cohesive force between the large primary particles of the secondary small particles is smaller than the cohesive force between the fine primary particles of the secondary large particles.

[0056] Therefore, during rolling, the large primary particles of the secondary small particles fall off and are separated before the secondary large particles crack, improving the cracking phenomenon of the secondary large particles. The separated small particles themselves are strong and do not crack, and the exposed surfaces are coated with a lithium M oxide layer, unlike the fine primary particles that make up the secondary large particles, so there is little deterioration in life characteristics.

[0057] M of the lithium M oxide coating layer may be at least one selected from the group consisting of boron and cobalt, and the content of M of the lithium M oxide coating layer may be, but is not limited to, 0.05 to 10 parts by weight based on 100 parts by weight of the secondary small particles.

[0058] The lithium M oxide coating layer is formed by reacting the M-containing precursor for forming the coating layer with the lithium impurities remaining on the surface of the large primary particles under an oxygen atmosphere, as described below. Such a coating layer can be formed in a stable spinel phase. As a result, even if the secondary small particles are not treated through a water washing process, the lithium impurities remaining on the surface are converted into lithium M oxide, thereby reducing the content of lithium impurities and improving the phenomenon of output reduction.

[0059] <Positive Electrode Active Material Containing Secondary Large Particles and Secondary Small Particles> In the cathode active material of the present invention including both the secondary large particles and the secondary small particles having the above-mentioned properties, the average particle size (D50) of the secondary large particles:the average particle size (D50) of the secondary small particles may be 5:1 to 2:1. Also, the content of the secondary small particles may be 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles.

[0060] Of course, the positive electrode active material may further include positive electrode active materials having different average particle sizes in addition to the secondary large particles and secondary small particles having the above-mentioned characteristics, as long as the object of the present invention is not impaired.

[0061] <Method of manufacturing positive electrode active material> The positive electrode active material according to an embodiment of the present invention may be prepared by the following method, but is not limited thereto.

[0062] A transition metal-containing solution containing nickel, cobalt, manganese and Q (Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti and Zr) in a predetermined molar ratio is mixed with an aqueous ammonia solution and an aqueous base solution to form transition metal hydroxide precursor particles, which are separated and dried, and then pulverized to have a predetermined average particle size (D50) (Step S1).

[0063] Since Q is an optional component, a specific description will be given of a case in which Q is not included.

[0064] First, a positive electrode active material precursor containing nickel (Ni), cobalt (Co) and manganese (Mn) is prepared.

[0065] In this case, the precursor for producing the positive electrode active material may be a commercially available positive electrode active material precursor, or may be produced by a method for producing a positive electrode active material precursor known in the art.

[0066] For example, the precursor may be prepared by adding an ammonium cation-containing chelating agent and a basic compound to a transition metal solution containing a nickel-containing source material, a cobalt-containing source material, and a manganese-containing source material, and then subjecting the mixture to a coprecipitation reaction.

[0067] The nickel-containing source material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salts, nickel halides, or combinations thereof.

[0068] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and may be, but is not limited to, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof.

[0069] The manganese-containing source material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically, manganese oxide such as Mn2O3, MnO2, Mn3O4, etc.; manganese salt such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0070] The transition metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, or may be prepared by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and the manganese-containing raw material.

[0071] The ammonium cation-containing chelating agent may be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3, or a combination thereof, but is not limited thereto. Meanwhile, the ammonium cation-containing chelating agent may be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.

[0072] The basic aqueous solution may be an aqueous solution of a basic compound, such as an alkali metal or alkaline earth metal hydroxide, a hydrate thereof, or a combination thereof, such as NaOH, KOH, or Ca(OH)2, etc. In this case, the solvent may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.

[0073] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount such that the pH of the metal solution becomes 9 to 12.

[0074] The transition metal hydroxide precursor particles may be prepared by mixing the transition metal-containing solution including nickel, cobalt, and manganese, an aqueous ammonia solution, and an aqueous base solution, and subjecting the mixture to a coprecipitation reaction.

[0075] In this case, the coprecipitation reaction can be carried out in an inert atmosphere such as nitrogen or argon at a temperature of 25°C to 60°C.

[0076] The transition metal hydroxide precursor particles produced are separated and dried in a reactor, and then pulverized to a predetermined average particle size (D50) through the process described below to form secondary small particles having the desired average particle size.

[0077] The crushed transition metal hydroxide precursor particles are then mixed with a lithium source material and calcined in an oxygen atmosphere to produce Li a Ni 1-b-c-d Co b Mn c Qd O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and producing core fine particles in which huge primary particles having an average particle diameter (D50) of 0.5 to 3 μm are aggregated (step S2).

[0078] In this way, by manufacturing - pulverizing - firing the precursor particles in steps (S1) and (S2), core fine particles in which huge primary particles having a predetermined average particle diameter are aggregated can be manufactured.

[0079] In the said step (S2), as the lithium raw material substance, lithium - containing sulfates, nitrates, acetates, carbonates, oxalates, citrates, halides, hydroxides, or oxy - hydroxides, etc. can be used, and there is no particular limitation as long as it is soluble in water. Specifically, the lithium raw material substance can be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, etc., and any one or a mixture of two or more of these can be used.

[0080] In the case of high - content nickel (high - Ni) NCM - based lithium composite transition metal oxide in which the content of nickel (Ni) is 80 mol% or more, firing can be performed at 790 to 950 °C and can be carried out for 5 to 35 hours in an oxygen atmosphere. In this specification, the oxygen atmosphere means an atmosphere including the air atmosphere and containing oxygen to a sufficient degree for firing. In particular, it is desirable to perform the firing in an atmosphere where the oxygen partial pressure is higher than the air atmosphere.

[0081] Next, a solution of a precursor containing one or more selected from the group consisting of boron, cobalt, manganese, and magnesium is mixed with the core small particles, which are then sprayed and dried using a spray dryer, and then sintered in an oxygen atmosphere to produce secondary small particles having an average particle size (D50) of 1 to 10 μm, which are formed by agglomeration of large primary particles having an average particle size (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface (step S3).

[0082] A precursor containing boron may be boric acid (H3BO3), and a precursor containing cobalt may be cobalt nitrate, etc. Solutions of these precursors may be prepared, for example, by dissolving the precursor in a solvent such as ultrapure water (DI water) or ethanol.

[0083] By mixing the precursor solution with the small core particles prepared in step (S2), and then spraying and drying using a spray dryer, it is possible to prepare particles in which the small core particles coated with the precursor are aggregated into a desired size.

[0084] In an oxygen atmosphere, a lithium M oxide coating layer is formed on some or all of the surfaces of the produced particles.

[0085] The lithium M oxide coating layer is formed by reacting the M-containing precursor for forming the coating layer with the lithium impurities remaining on the surface of the core small particles under an oxygen atmosphere. Such a coating layer can be formed in a stable spinel phase. As a result, even if the secondary small particles are not treated through a water washing process, the lithium impurities remaining on the surface are converted into lithium M oxide, thereby reducing the content of lithium impurities and improving the phenomenon of output reduction.

[0086] The firing for forming the coating layer may be performed at a temperature of 350 to 600° C. for 3 to 6 hours, but is not limited thereto.

[0087] By the above-described steps (S1) to (S3), the secondary fine particles having the above-described properties can be produced.

[0088] The produced secondary fine particles are Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0 ≤ a ≤ 1.5, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.2, -0.1 ≤ δ ≤ 1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), and by mixing with secondary large particles having an average particle diameter (D50) of 5 to 20 μm formed by aggregating fine primary particles having an average particle diameter (D50) smaller than that of the giant primary particles, the positive electrode active material of the present invention can be produced.

[0089] The secondary large particles may be purchased commercially and used, or may be directly produced and used using a known coprecipitation method. More specifically, generally, secondary particles in which a plurality of high-content nickel-based composite transition metal hydroxide particles are aggregated are obtained as a precursor using a coprecipitation method well known in the art, mixed with a lithium source, and then fired to produce them. Here, methods for controlling the composition of the precursor using the coprecipitation method, the type of lithium source, etc. can follow the common general technical knowledge in the art.

[0090] <Positive Electrode and Lithium Secondary Battery> According to still another aspect of the present invention, there are provided a positive electrode for a lithium secondary battery including the positive electrode active material and a lithium secondary battery.

[0091] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material of the present invention described above.

[0092] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0093] The positive electrode active material layer may further include a positive electrode active material formed of large single particles or secondary particles formed by agglomeration of conventional fine primary particles in addition to the above-mentioned positive electrode active material, and may further include a conductive material and a binder.

[0094] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one of these may be used alone or a mixture of two or more of them may be used. The conductive material may usually be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0095] The binder also serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0096] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode may be manufactured by coating a composition for forming a positive electrode active material layer, which includes the positive electrode active material and, optionally, a binder and a conductive material, on a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0097] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into consideration the coating thickness of the slurry and the manufacturing yield, and to provide a viscosity that allows excellent thickness uniformity to be achieved when the slurry is applied to manufacture a positive electrode.

[0098] Alternatively, the positive electrode may be manufactured by casting the composition for forming a positive electrode active material layer on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0099] According to yet another aspect of the present invention, there is provided an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0100] The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0101] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0102] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to increase the adhesive strength of the negative electrode active material, as in the case of the positive electrode current collector. For example, it may be used in various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0103] The negative electrode active material layer may include a negative electrode active material and, optionally, a binder and a conductive material, and may be manufactured, for example, by coating a negative electrode forming composition including a negative electrode active material and, optionally, a binder and a conductive material on a negative electrode current collector and drying the composition, or by casting the negative electrode forming composition on a separate support and then peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0104] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, scaly, spherical, or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal-based coke.

[0105] Additionally, the binder and conductive material are the same as those described above for the positive electrode.

[0106] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0107] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0108] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0109] The organic solvent may be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move.Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), or propylene carbonate (PC); an alcohol solvent such as ethyl alcohol or isopropyl alcohol; a nitrile such as R-CN (R is a C2-C20 straight-chain, branched, or cyclic hydrocarbon group, which may contain a double-bonded aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; or a sulfolane. Among them, carbonate-based solvents are preferable, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant capable of improving the charge / discharge performance of a battery and a low-viscosity linear carbonate-based compound (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is more preferable. In this case, it is preferable to mix the cyclic carbonate and the linear carbonate in a volume ratio of about 1:1 to about 1:9 for excellent electrolyte performance.

[0110] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt may be within a range of 0.1 to 2.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore exhibits excellent electrolyte performance and allows lithium ions to move effectively.

[0111] In addition to the electrolyte components described above, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving battery life characteristics, suppressing a decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.

[0112] The lithium secondary battery including the positive electrode active material according to the present invention has excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs), etc.

[0113] According to yet another aspect of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0114] The battery module or battery pack may be used as a power source for one or more medium to large devices including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.

[0115] The present invention will now be described in detail with reference to exemplary embodiments so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments described below.

[0116] <Example 1> (Production of secondary large particles) A secondary particle in which a plurality of high-content nickel-based composite transition metal hydroxide particles are assembled is obtained as a precursor by using a coprecipitation method well known in the art, and the precursor is mixed with a lithium source and then calcined to obtain LiNi 0.8 Co 0.1 Mn 0.1 Secondary large particles having an average particle size (D50) of 15 μm were prepared by agglomeration of fine primary particles made of O2 and having an average particle size (D50) of several hundreds of nm.

[0117] (Production of secondary small particles) After 4 liters of distilled water was put into a coprecipitation reactor (volume 20 L), 100 mL of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50 ° C. Then, a 3.2 mol / L transition metal solution in which NiSO4, CoSO4, and MnSO4 were mixed so that the molar ratio of nickel:cobalt:manganese was 0.8:0.1:0.1 was continuously added to the reactor at 300 mL / hr and 28 wt% aqueous ammonia solution at 42 mL / hr. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added to maintain the pH at 9. The coprecipitation reaction was carried out for 10 hours to form precursor particles. The precursor particles were separated and washed, and then dried in an oven at 130 ° C to produce a precursor.

[0118] Ni synthesized by coprecipitation reaction 0.8 Co0.1 Mn 0.1 The (OH)2 precursor was put into a mixer and crushed to a size of about 1 μm. The crushed precursor was then mixed with LiOH in a molar ratio of 1.05, and heat-treated at 800 °C for 15 hours in an oxygen atmosphere to produce LiNi 0.8 Co 0.1 Mn 0.1 O2-lithium composite transition metal oxide was prepared.

[0119] 100g of the produced cathode material was mixed with a solution of 30g of H3BO3 dissolved in ethanol as a coating source, sprayed and dried using a spray dryer, and then fired at 450℃ for 5 hours in an oxygen atmosphere to obtain the final secondary small particles. The obtained secondary small particles were particles with an average particle size (D50) of 4μm, formed by the aggregation of large primary particles with an average particle size (D50) of 1μm.

[0120] (Production of positive electrode active material) The secondary large particles and secondary small particles obtained by the above-mentioned method were mixed in a weight ratio of 7:3 to prepare a bimodal positive electrode active material.

[0121] <Example 2> (Production of secondary large particles) It was produced in the same manner as in Example 1.

[0122] (Production of secondary small particles) After 4 liters of distilled water was put into a coprecipitation reactor (volume 20 L), 100 mL of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50 ° C. Then, a 3.2 mol / L transition metal solution in which NiSO4, CoSO4, and MnSO4 were mixed so that the molar ratio of nickel:cobalt:manganese was 0.8:0.1:0.1 was continuously added to the reactor at 300 mL / hr and 28 wt% aqueous ammonia solution at 42 mL / hr. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added to maintain the pH at 9. The coprecipitation reaction was carried out for 10 hours to form precursor particles. The precursor particles were separated and washed, and then dried in an oven at 130 ° C to produce a precursor.

[0123] Ni synthesized by coprecipitation reaction 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor was put into a mixer and crushed to a size of about 1 μm. The crushed precursor was then mixed with LiOH in a molar ratio of 1.05, and heat-treated at 800 °C for 15 hours in an oxygen atmosphere to produce LiNi 0.8 Co 0.1 Mn 0.1 O2-lithium composite transition metal oxide was prepared.

[0124] 100g of the produced cathode material was mixed with a solution of 60g of H3BO3 dissolved in ethanol as a coating source, sprayed and dried using a spray dryer, and then fired at 450℃ for 5 hours in an oxygen atmosphere to obtain the final secondary small particles. The obtained secondary small particles were particles with an average particle size (D50) of 4μm, formed by the aggregation of large primary particles with an average particle size (D50) of 1μm.

[0125] (Production of positive electrode active material) The secondary large particles and secondary small particles obtained by the above-mentioned method were mixed in a weight ratio of 7:3 to prepare a bimodal positive electrode active material.

[0126] <Example 3> (Production of secondary large particles) It was produced in the same manner as in Example 1.

[0127] (Production of secondary small particles) After 4 liters of distilled water was put into a coprecipitation reactor (volume 20 L), 100 mL of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50 ° C. Then, a 3.2 mol / L transition metal solution in which NiSO4, CoSO4, and MnSO4 were mixed so that the molar ratio of nickel:cobalt:manganese was 0.8:0.1:0.1 was continuously added to the reactor at 300 mL / hr and 28 wt% aqueous ammonia solution at 42 mL / hr. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added to maintain the pH at 9. The coprecipitation reaction was carried out for 10 hours to form precursor particles. The precursor particles were separated and washed, and then dried in an oven at 130 ° C to produce a precursor.

[0128] Ni synthesized by coprecipitation reaction 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor was put into a mixer and crushed to a size of about 1 μm. The crushed precursor was then mixed with LiOH in a molar ratio of 1.05, and heat-treated at 800 °C for 15 hours in an oxygen atmosphere to produce LiNi 0.8 Co 0.1 Mn 0.1 O2-lithium composite transition metal oxide was prepared.

[0129] 100g of the produced cathode material was mixed with a solution of 30g of manganese acetate dissolved in ethanol as a coating source, sprayed and dried using a spray dryer, and then fired at 450℃ for 5 hours in an oxygen atmosphere to obtain the final secondary small particles. The obtained secondary small particles were particles with an average particle size (D50) of 4μm, formed by the aggregation of large primary particles with an average particle size (D50) of 1μm.

[0130] (Production of positive electrode active material) The secondary large particles and secondary small particles obtained by the above-mentioned method were mixed in a weight ratio of 7:3 to prepare a bimodal positive electrode active material.

[0131] <Comparative Example 1> A conventional bimodal positive electrode active material (weight ratio of secondary large particles to secondary small particles = 7:3) was produced using secondary small particles having an average particle size (D50) of 4 μm, which were agglomerates of primary fine particles produced by the method for producing secondary large particles in Example 2, instead of the secondary small particles in Example 1.

[0132] <Comparative Example 2> A bimodal positive electrode active material was produced in the same manner as in Example 1, except that the secondary small particles in Example 1 were replaced with single particles produced by the following method.

[0133] After 4 liters of distilled water was added to a coprecipitation reactor (volume 20 L), 100 ml of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50°C. Then, a 3.2 mol / L transition metal solution, which was a mixture of NiSO4, CoSO4, and MnSO4 with a nickel:cobalt:manganese molar ratio of 0.8:0.1:0.1, was added at 300 ml / hr, and a 28 wt% aqueous ammonia solution was added at 42 ml / hr. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added to maintain the pH at 9.5.

[0134] The precursor particles were formed by coprecipitation for 24 hours, and the precursor particles were separated, washed, and then dried in an oven at 130° C. to produce the precursor.

[0135] The precursor was mixed with LiOH to achieve a Li / Metal (Ni, Co, Mn) molar ratio of 1.15, and the mixed powder was placed in an alumina crucible for heat treatment. It was then fired at 850°C for 15 hours to produce a single particle type positive electrode active material (D50=4μm).

[0136] [Experimental Example 1: Observation of Positive Electrode Active Material] A schematic diagram of the secondary large particles according to the present invention and an SEM image of the secondary large particles used in Example 1 are shown in FIG. 1a and FIG. 1b, respectively.

[0137] A schematic diagram of the secondary small particles according to the present invention and an SEM image of the secondary small particles used in Example 1 are shown in FIG. 2a and FIG. 2b, respectively.

[0138] A schematic diagram of a single particle used in Comparative Example 2 and an SEM image of the single particle are shown in FIG. 3a and FIG. 3b, respectively.

[0139] [Experimental Example 2: Average particle size] D50 is defined as the particle size at 50% of the particle size distribution and was measured using a laser diffraction method.

[0140] [Experimental Example 3: Crystal size of primary particles] The samples were measured using a Bruker Endeavor (CuKα, λ = 1.54 A°) equipped with a LynxEye XE-T position sensitive detector at FDS 0.5°, over the 2θ = 15° to 90° range with a step size of 0.02° and a total scan time of 20 min.

[0141] The measured data were subjected to Rietveld refinement, taking into account the charge (+3 for metals at transition metal sites, +2 for Ni at Li sites) and cation mixing from each site. For crystal size analysis, instrumental broadening was considered using the Fundamental Parameter Approach (FPA) implemented in the TOPAS program made by Bruker, and the entire peak in the measurement range was used for fitting. Peak morphology was fitted using only the Lorenzian contribution in the First Principle (FP) of the peak types available in TOPAS, and strain was not considered at this time.

[0142] [Experimental Example 4: Measurement of rolling density] The rolling density was measured using HPRM-1000. Specifically, 5 g of the positive electrode active material of each of the examples and comparative examples was placed in a cylindrical mold, and the mold filled with the positive electrode active material was pressurized with 9 tons. The height of the pressed mold was then measured with a vernier caliper to obtain the rolling density.

[0143] The measured rolling densities of the examples and comparative examples are shown in Table 1 below.

[0144] [Table 1]

[0145] [Experimental Example 5: Measurement of crack occurrence] A positive electrode was prepared using the positive electrode active materials according to the examples and comparative examples, and the rolled electrode was sintered in a sintering furnace at 500°C for 10 hours, after which only the remaining active material was obtained. PSD measurement was performed using MT3000 manufactured by Microtrac, and the area of ​​1 μm or less was measured.

[0146] [Table 2]

[0147] [Experimental Example 6: Measurement of life characteristics] Positive electrodes were manufactured using the positive electrode active materials according to the examples and comparative examples, and the capacity retention rate was measured as follows: A negative electrode active material was a mixture of artificial graphite and natural graphite mixed in a ratio of 5:5, a conductive material was Super P, and a binder was mixed in a weight ratio of 96:1:3 to manufacture a negative electrode slurry, which was then applied to one side of a copper current collector, dried at 130°C, and rolled to a porosity of 30% to manufacture a negative electrode.

[0148] A porous polyethylene separator was interposed between the positive and negative electrodes prepared as above to prepare an electrode assembly. The electrode assembly was then placed inside a case, and an electrolyte was then injected into the case to prepare a lithium secondary battery.

[0149] The electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0 M in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (EC / EMC / DEC mixed volume ratio = 3 / 4 / 3).

[0150] The manufactured lithium secondary battery full cell was charged at 0.5C in CC (constant current)-CV (constant voltage) mode at 45℃ up to 4.2V, and discharged at a constant current of 1C down to 3.0V, and the capacity retention rate was measured after 100 charge-discharge experiments to evaluate the life characteristics.

[0151] [Table 3]

Claims

1. secondary small particles having an average particle size (D50) of 1 to 10 μm, which are formed by agglomeration of large primary particles having an average particle size (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface; and secondary large particles having an average particle size (D50) of 5 to 20 μm formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the large primary particles, The large primary particles and the fine primary particles are each Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0<b<0.2, 0<c<0.2, 0≦d≦0.1, 0<b+c+d≦0.2, −0.1≦δ≦1.0, and Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr), The positive electrode active material for a lithium secondary battery, wherein the cohesive force between the large primary particles of the secondary small particles is smaller than the cohesive force between the fine primary particles of the secondary large particles.

2. 2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein the ratio of the average particle size (D50) of the secondary large particles to the average particle size (D50) of the secondary small particles is 5:1 to 2:

1.

3. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of the secondary small particles is 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles.

4. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein M of the lithium M oxide coating layer is at least one selected from the group consisting of boron and cobalt.

5. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium M oxide coating layer has an M content of 0.05 to 10 parts by weight based on 100 parts by weight of the secondary small particles.

6. A method for producing a positive electrode active material for a lithium secondary battery, comprising: The positive electrode active material for a lithium secondary battery is secondary small particles having an average particle size (D50) of 1 to 10 μm, which are formed by agglomeration of large primary particles having an average particle size (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface; and secondary large particles having an average particle size (D50) of 5 to 20 μm formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the large primary particles, The large primary particles and the fine primary particles are each represented by Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0<b<0.2, 0<c<0.2, 0≦d≦0.1, 0<b+c+d≦0.2, −0.1≦δ≦1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr); (S1) mixing a transition metal-containing solution containing nickel, cobalt, manganese, and Q (Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti, and Zr) in a predetermined molar ratio with an aqueous ammonia solution and an aqueous base solution to form transition metal hydroxide precursor particles, separating and drying the resulting particles, and then pulverizing the transition metal hydroxide precursor particles to have a predetermined average particle size (D50); (S2) The pulverized transition metal hydroxide precursor particles are mixed with a lithium source material and fired in an oxygen atmosphere to obtain Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0<b<0.2, 0<c<0.2, 0≦d≦0.1, 0<b+c+d≦0.2, -0.1≦δ≦1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti and Zr) and having an average particle size (D50) of 0.5 to 3 μm; (S3) mixing the core small particles with a precursor solution containing one or more selected from the group consisting of boron, cobalt, manganese, and magnesium, spraying and drying the mixture using a spray dryer, and then firing the mixture in an oxygen atmosphere to produce secondary small particles having an average particle size (D50) of 1 to 10 μm, which are formed by agglomeration of large primary particles having an average particle size (D50) of 0.5 to 3 μm and a lithium M oxide coating layer (M is one or more selected from the group consisting of boron, cobalt, manganese, and magnesium) formed on a part or all of the surface; (S4) Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ (1.0≦a≦1.5, 0<b<0.2, 0<c<0.2, 0≦d≦0.1, 0<b+c+d≦0.2, -0.1≦δ≦1.0, Q is one or more metal elements selected from the group consisting of Al, Mg, V, Ti and Zr), and having an average particle size (D50) of 5 to 20 μm formed by agglomerating fine primary particles having an average particle size (D50) smaller than that of the giant primary particles, and mixing the secondary small particles with the giant primary particles.

7. 7. The method for producing a positive electrode active material for a lithium secondary battery according to claim 6, wherein the ratio of the average particle size (D50) of the secondary large particles to the average particle size (D50) of the secondary small particles is 5:1 to 2:

1.

8. 7. The method of claim 6, wherein the content of the secondary small particles is 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles.

9. 7. The method for producing a positive electrode active material for a lithium secondary battery according to claim 6, wherein M of the lithium M oxide coating layer is at least one selected from the group consisting of boron and cobalt.

10. 7. The method of claim 6, wherein the lithium M oxide coating layer has an M content of 0.05 to 10 parts by weight based on 100 parts by weight of the secondary small particles.

11. A positive electrode for a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery according to claim 1 .

12. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 11.

Citation Information

Patent Citations

  • Non-aqueous electrolyte secondary battery

    WO2020202745A1